ECONOMIC DIPLOMACY OF INDIA WITH CENTRAL ASIAN COUNTRIES: CONDITION AND PERSPECTIVES OF DEVELOPMENT (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Relationships of India with Central Asian countries date back to ancient times and, in most parts, their history is intersected with each other. Their collaboration started with The Silk Road and reached its highest level during the Mughal Empire. After acquiring independency and the collapse of Soviet Union Central Asian countries started their integration with India from scratch. In this article, economic relations of India with Central Asian Countries, struggles that they are currently experiencing, as well as, future perspectives of this economic collaboration are studied and some suggestions have been made.